EFEKTIVITAS PENGGUNAAN VIDEO PEMBELAJARAN ANATOMI TERHADAP KESIAPAN MAHASISWA KEDOKTERAN MENGIKUTI PRATIKUM ANATOMI SISTEM REPRODUKSI PRIA: (Studi pada mahasiswa kedokteran Universitas Abdurrab) - May Valzon; Tasha Haviva Suhaila; Huda Marlina Wati (LPPM Universitas Abdurrab, 2024)
Background: The competencies that medical students must have at the academic level are the realm of biomedical science, medical humanities, clinical medical science and public health science, by paying attention to the principles of scientific method and curriculum principles. Biomedical science is a branch of medical science consisting of anatomy, physiology, and biochemistry. Anatomy is a medical language that is very important for medical students to study the normal body structure starting from the shape, size, location, supporting elements and their relationship with the surrounding structure. Evaluation of medical education institutions shows that less time is spent studying anatomy. In addition, the material and limitations of props such as guidebooks that do not have high image quality make it difficult for students to understand the material contained in the book. These day, thanks to technological innovations, there have been many changes in the teaching and learning process. Advances in computer and smartphone technology allow the development of various multimedia learning environments, including video learning that can be repeated on smartphones, besides that multimedia can increase working memory capacity. Objectibve: Analyse the effectiveness of male reproductive sistem anatomy practicum learning videos to improve student learning achievement in anatomy learning in medical students. Method:This research method is an experimental method with a cross-over design. The population of this research is second-year students of the 2023/2024 academic year, the Faculty of Medicine, Abdurrab University with the total sampling method. Results: The results of the Mann-Whitney comparative test showed that there was no significant difference between the group using video learning media and the group using the module learning media (P-value = 0.518). The average percentage of external male reproductive sistem kuis given treatment using modules and videos was 68.63 and 69.03. Meanwhile, the average percentage of kuis of the internal male reproductive sistem given treatment using modules and videos is 73.57 and 68.00. Conclusion: The use of video is no more effective as a medium for learning anatomy practicums, especially in learning the male reproductive system module at the Faculty of Medicine, Abdurrab University.